2006
DOI: 10.1159/000091453
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Prohepcidin Positively Correlates with Hematocrit in Chronic Hemodialysis Patients

Abstract: Background/Aims: Experimental studies have demonstrated interleukin-6 and iron load induce expression of hepcidin (an iron regulatory peptide), whereas anemia and erythropoietin (EPO) suppress its expression. We are the first to explore the relationships of plasma prohepcidin (the pro-hormone of hepcidin) in patients undergoing chronic hemodialysis (HD). Methods: We enrolled 71 chronic HD patients. During the preceding 3 months before enrollment, they all had steady weekly levels of haematocrit (Hct) and fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 29 publications
2
34
1
Order By: Relevance
“…5,12,20 Similar inconsistencies are apparent in the literature as to the relationship between pro-hepcidin and hemoglobin/hematocrit levels: either inverse 13,21 or direct, positive correlations. 22 In contrast to these studies, we observed no signifi cant correlation between pro-hepcidin and hemoglobin even. Again, in this controversial area, our data are not singular, as Taes et al-in pre-dialysis patients-also failed to detect a relation between pro-hepcidin levels and hematocrit.…”
Section: Discussioncontrasting
confidence: 95%
“…5,12,20 Similar inconsistencies are apparent in the literature as to the relationship between pro-hepcidin and hemoglobin/hematocrit levels: either inverse 13,21 or direct, positive correlations. 22 In contrast to these studies, we observed no signifi cant correlation between pro-hepcidin and hemoglobin even. Again, in this controversial area, our data are not singular, as Taes et al-in pre-dialysis patients-also failed to detect a relation between pro-hepcidin levels and hematocrit.…”
Section: Discussioncontrasting
confidence: 95%
“…The increased hepcidin expression during inflammation and infection explains sequestration of iron in the macrophages and inhibition of intestinal iron absorption, the two hallmarks of the anemia of inflammation, which is normocytic or microcytic and hypochromic. [25][26][27] HD patient's non-responders to rhEPO therapy presented a mild anemia, even with the administration of higher rhEPO doses. This anemia is hypochromic (decreased MCH and MCHC), and is associated with a more accentuated anisocytosis than in responder patients.…”
Section: Discussionmentioning
confidence: 99%
“…They found no relation between prohepcidin and ferritin and TSAT. Hsu et al [18] also demonstrated that plasma prohepcidin correlated positively with hematocrit (Hct) but negatively with rHuEPO dosage. In contrast, Malyszko et al [19] showed a positive association between prohepcidin and rHuEPO dose in the HD patients treated with rHuEPO.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is likely therefore that prohepcidin may not be a reliable marker for assessing rHuEPO responsiveness in HD patients. In addition, limitations of this ELISA system cannot be ruled out as a possible explanation for the previous inconsistent results between prohepcidin and rHuEPO responsiveness and renal anemia [9,18,19,20]. …”
Section: Discussionmentioning
confidence: 99%